2022
DOI: 10.18662/rrem/14.4/626
|View full text |Cite
|
Sign up to set email alerts
|

A Future Primary School Teacher Competence Building Model through Application of Innovative Technologies

Abstract: Nowadays in the context of innovations in the education system it is necessary to substantiate the organizational and pedagogical conditions for the formation of mathematical competence. These changes necessitated the development of a model for the formation of the mathematical competence of future primary school teachers by means of innovative technologies. The purpose of the article is to get acquainted with the components of primary school teachers’ professional competence, to characterize the content of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…We haven't studied this aspect, but the level of communication skills of EG students increased significantly compared to EG. Baytak et al (2011), Zaporozhchenko et al (2022 found that the majority of students believe that the integration of technology into the curriculum plays an important role in improving their learning abilities. Integrating technology into education is also beneficial for students with special needs.…”
Section: Discussionmentioning
confidence: 99%
“…We haven't studied this aspect, but the level of communication skills of EG students increased significantly compared to EG. Baytak et al (2011), Zaporozhchenko et al (2022 found that the majority of students believe that the integration of technology into the curriculum plays an important role in improving their learning abilities. Integrating technology into education is also beneficial for students with special needs.…”
Section: Discussionmentioning
confidence: 99%